The Oxford Handbook of the Sociology of Africa 2022
DOI: 10.1093/oxfordhb/9780197608494.013.12
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health in Africa

Abstract: This chapter examines the social determinants of health (SDH) in Africa. It highlights some theoretical perspectives relevant to understanding the SDH, including the production of health and structural and system approaches. The chapter argues that the high prevalence of both communicable and noncommunicable diseases in Africa is a consequence of adverse social forces that predispose people to various diseases. Africans live in challenging social situations and have a comparatively high disease burden. Most ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…CS prevalence similarly differs between rural and urban Nigeria across geographic, educational, and socioeconomic factors. The substantial divergence in CS utilisation observed in our study strongly suggests limited access or potential barriers in rural Nigerian settings-consistent with the concept of social inequities occasioned by geographic and socioeconomic inequalities 39 . This observation gains further support across regions in the country.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…CS prevalence similarly differs between rural and urban Nigeria across geographic, educational, and socioeconomic factors. The substantial divergence in CS utilisation observed in our study strongly suggests limited access or potential barriers in rural Nigerian settings-consistent with the concept of social inequities occasioned by geographic and socioeconomic inequalities 39 . This observation gains further support across regions in the country.…”
Section: Discussionsupporting
confidence: 82%
“…This position aligns with the ndings of a study on user fee exemption in Nigeria, which revealed lower CS rates among low-income women, notwithstanding the availability of free maternal healthcare services 23 . Thus, a multifaceted intervention strategy, addressing systemic issues (social injustices, for example), promoting high-quality education, ensuring equal opportunities, creating job prospects, and empowering individuals and communities to enhance their economic well-being, is likely to yield more effective and enduring results 39 . Moreover, the distinct urban factor related to religious a liations underscores the need for faith-based and culturally sensitive health communication strategies.…”
Section: Implications and Recommendationsmentioning
confidence: 99%